Pengaruh Pendidikan dan Pelatihan Kesehatan Gigi dan Mulut serta Gigi Tiruan Pada Lansia di Panti Werdha Berea Kedoya - Falatehan, Niko; Yusra, Yohana; Chandra Dwidjayanti, Siti; Faaudah Amin, Meiny; Ariwibowo, Taufiq (Fakultas Kedokteran Gigi, Universitas Trisakti bekerjasama dengan Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Trisakti, 2024)
Elderly are people aged 60 years or more. According to Riskesdas, the highest prevalence of tooth loss in Indonesia is in the age group over 60 years, specifically at 30.6%. Prosthodontic treatment can improve a patient's oral health, improve their masticatory and speech functions, and improve their aesthetics. However, the use of dentures requires proper care. The elderly need to be aware of how to maintain oral health and care for dentures to ensure its longevity. The purpose of this activity is to increase knowledge and change attitudes and behaviors concerning dental health care, denture care and oral hygiene in the elderly. In this activity, audio visual training techniques are applied by using powerpoint and videos as training tools to improve the retention of counseling materials by the elderly and avoid saturation. The delivery of materials is conducted using a language that is easily understood by the elderly. Based on the results of the pretest and posttest, this activity shows an increase in knowledge as well as the enthusiasm of the participants in asking questions about counseling and training related to maintaining oral health and the mouth as well as dentures. A good level of success can be achieved through this activity as it is supported by appropriate methods and good communication between the implementing team and the community.